Long‐Term Recurrence‐Free Outcome After Doxycycline Pleurodesis With Pulmonary Rehabilitation and Nutritional Support in an Underweight Patient With COPD : A Case Report - Kemas Rakhmat Notariza; Prasenohadi Pradono; Siti Chandra Widjanantie; Elfina Rachmi; Agus Dwi Susanto (Respirology Case Reports, 2026)
ABSTRACT Secondary spontaneous pneumothorax (SSP), a complication of chronic obstructive pulmonary disease (COPD), recurs more frequently in underweight patients. This case report describes a 63‐year‐old malnourished man with COPD presenting with recurrent left‐sided SSP shortly after hospital discharge for a previous episode. Following chest tube reinsertion and complete lung re‐expansion, chemical pleurodesis was performed using 1000 mg doxycycline in saline. Transient pleuritic pain was controlled with intravenous ketorolac and intrapleural lidocaine. No other immediate or delayed adverse events occurred. In parallel, pulmonary rehabilitation, including breathing exercises, posture correction, moderate‐intensity endurance and inspiratory muscle training, was initiated alongside nutritional repletion with a respiratory‐specific oral nutritional supplement. Over a 22‐month follow‐up, the patient remained free of SSP recurrence, with improved functional capacity and weight gain. This report describes a long‐term recurrence‐free outcome after doxycycline pleurodesis combined with pulmonary rehabilitation and nutritional support in an underweight patient with COPD.